(untitled) (Research, Society and Development, 2022)
The Covid-19 pandemic is considered the most significant health crisis in recent world history, triggering impacts on the health and economy of nations. Thus, the study aims to evaluate the level of Transparency of Emergency Contracts in combating the pandemic in the Southern Coastal Identity Territory Region, Bahia. A method developed by Transparency International Brazil in partnership with the Federal Audit Court allows establishing the level of transparency of Municipalities through data collection through official portals of municipal governments. From the publication of the first result of the evaluation, it was noted that the municipalities sought to meet the legal determinations. The second result’s publication identified competitiveness in the advertising of information among the cities and that the research performed a pedagogical function for the municipal managers.